MEMAKSIMALKAN POTENSI ZAKAT MELALUI PENINGKATAN AKUNTABILITAS LEMBAGA PENGELOLA ZAKAT - Tambunan, Jannus (Islamic Circle, 2021)
Increased accountability zakat management institutions are urgently required, as zakat management institutions accountable, will be able to increase confidence muzakki that pay their zakat through zakat management institutions, so that the utilization of zakat can be measured and properly channeled. Increased accountability zakat management institutions can be done through increased supervision and internal control systems.